2000
DOI: 10.1016/s1074-7613(00)00042-x
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of AML1 Affects the Temporal and Spatial Generation of Hematopoietic Stem Cells in the Mouse Embryo

Abstract: The AML1:CBFbeta transcription factor complex is essential for definitive hematopoiesis. Null mutations in mouse AML1 result in midgestational lethality with a complete lack of fetal liver hematopoiesis. While the cell autonomous nature and expression pattern of AML1 suggest an intrinsic role for this transcription factor in the developing hematopoietic system, no direct link to a functional cell type has been made. Here, we examine the consequences of AML1 loss in hematopoietic stem cells (HSC) of the mouse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
195
1
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 232 publications
(211 citation statements)
references
References 40 publications
11
195
1
4
Order By: Relevance
“…In the hemogenic arteries (dorsal aorta, vitelline and umbilical) endothelial Runx1 expression precedes the emergence of hematopoietic cells, which has been interpreted as Runx1 marking the hemogenic endothelium. In the absence of Runx1, hemogenic endothelium is still made but no definitive hematopoietic cells are formed [51][52][53][54][55][56]. Deletion of Runx1 in VE-Cadh + cells indicated that Runx1 is critically required in this population [28].…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
“…In the hemogenic arteries (dorsal aorta, vitelline and umbilical) endothelial Runx1 expression precedes the emergence of hematopoietic cells, which has been interpreted as Runx1 marking the hemogenic endothelium. In the absence of Runx1, hemogenic endothelium is still made but no definitive hematopoietic cells are formed [51][52][53][54][55][56]. Deletion of Runx1 in VE-Cadh + cells indicated that Runx1 is critically required in this population [28].…”
Section: Identification Of Hemogenic Endotheliummentioning
confidence: 99%
“…Consistent with this observation, mouse embryos with hemizygosity for the mutant AML1 allele have an increased number of hematopoietic stem cells associated to a decrease in committed progenitors, suggesting that haploinsufficiency of AML1 affects maturation and proliferation of hematopoietic cells. 131 On the other hand, acquired AML1 mutations are observed in 6-10% of sporadic AML and are found at similar frequency in adult and pediatric AML. Mutations are equally distributed between missense and nonsense mutations (resulting in truncated protein) in de novo AML.…”
Section: Aml1mentioning
confidence: 99%
“…The CBFb subunit is widely expressed (Golling et al, 1996;Ogawa et al, 1993;Wang et al, 1993), whereas AML1 expression during development is limited to hematopoietic stem cells, endothelial cells of the aortagonad-mesonephros, condrogenic centers, olfactory and gustatory mucosa and neural ganglion cells; while after organogenesis it is conĀ®ned to hematopoietic cells (Cai et al, 2000;Corsetti and Calabi, 1997;Simeone et al, 1995).…”
Section: Transcriptional Regulators Involved In Aml-associated Fusionmentioning
confidence: 99%